Microbial diversity of individual raindrops collected from simulated and natural precipitation events. (15th July 2019) - Garcia, Ellen B.; Hanlon, Regina; Makris, Melissa R.; Powers, Craig W.; Jimenez-Sanchez, Celia; Karatum, Osman; Marr, Linsey C.; Sands, David C.; Schmale, David G.
Abstract: Precipitation samples collected at or near the surface of the earth are composite samples of many different raindrops. Little is known about the abiotic and biotic components found within individual raindrops. To help fill this knowledge gap, we designed a system for collecting individual raindrops called the L iquid N itrogen A pparatus for I solating R aindrops (LNAIR). The LNAIR was used in a series of laboratory experiments to determine (1) determine the recovery volume of drops with known sizes and to (2) measure the viability of seeded-microbes from drops of different sizes. The LNAIR recovered an average of 73% of the initial drop volume for drops ranging from 5 μl to 50 μl, and the original and recovered mean volumes were significantly correlated (R 2 = 0.96). The viability of seeded ice-nucleating strains of Pseudomonas syringae and Fusarium avenaceum decreased after passage through the LNAIR, but the ice nucleation activity (INA) did not change. Moreover, the size (volume) of the droplet did not appear to have an effect on the viability of microbes after passage through the LNAIR, at least for the two strains of P. syringae tested. The LNAIR was then used in a series of field experiments to collect raindrops from simulated and natural precipitation events. The mean drop volume observed from six simulated rain events (SREs) was 9.4 μl ± 0.5, while the mean drop volume observed from four natural rain events (NREs) was 7.6 μl ± 0.4. Flow cytometer analysis showed that there was an average of 395 ± 103 DNA-containing particles per 10 μl of NRE drops (n = 6) and an average of 892 ± 171 DNA-containing particles per 10 μl of SRE drops (n = 4). NRE drops contained a similar range of particle sizes compared to SRE drops. Twenty seven percent (9/34) of the SRE drops and 28% (40/143) of the NRE drops collected with the LNAIR contained culturable microorganisms, but none of these displayed INA at −8 °C. Microbes cultured from individual NRE drops were identified to the level of genus using sequences. The genera Cladosporium (fungi) and Bacillus (bacteria) represented 22% (15/68) and 20% (19/68) of the microbes identified, respectively. One natural raindrop contained four different genera ( Bacillus, Trichoderma, Penicillium, and Cladosporium ). The LNAIR has the potential to increase our understanding of causal agents of precipitation processes. Highlights: Individual raindrops from precipitation events were isolated in liquid nitrogen. Ice nucleation activity did not change after passage through liquid nitrogen. Size distributions (in μl) were determined for simulated and natural raindrops. DNA-containing particles were quantified in natural raindrops. Microorganisms from natural rain events were identified, and some raindrops contained more than one genus.